DOMINASI KELOMPOK ETNIS TIONGHOA PADA BIDANG EKONOMI DI INDONESIA TAHUN 1986-2000 - Khoirul Huda; Bobi Hidayat (Swarnadwipa, 2020)
The purpose of this study is to describe the background of the domination of Chinese ethnicity in the economic sector in Indonesia in 1986-2000. To describe the development of Chinese ethnic economic domination in Indonesia in 1986-2000. To analyze the impact of the domination of Chinese ethnic groups on the economic sector on the Indonesian economy in 1986-2000. This research method using heuristict, library study, and data inteprtation method. This research was conducted at the UM Metro library by examining the literature on the economic dominance of Chinese Ethnics in Indonesia through source criticism. The results of this study indicate that the presence of Chinese people in Indonesia in trading indirectly affects the economic situation of the Indonesian nation. Chinese people have high persistence and struggle in running the economy. This made the Chinese economy dominate the indigenous economy. As an example in various regions of Indonesia, the majority of large companies are controlled by the Chinese, especially the assets owned and many Chinese have invested inIndonesian companies. In addition, Chinese trade is also very dominant, it can be seen that large scale traders are dominated by Chinese people, such as jewelry traders, building shops, and electronics stores.